2006
DOI: 10.1016/j.chemosphere.2005.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate (As) uptake by and distribution in two cultivars of winter wheat (Triticum aestivum L.)

Abstract: Two cultivars of winter wheat (Triticum aestivum L.) (Jing 411 and Lovrin 10) were used to investigate arsenate (As) uptake and distribution in plants grown in hydroponic culture and in the soil. Results showed that without As addition, Lovrin 10 had higher biomass than Jing 411 in the soil pot experiment; in the hydroponic experiment Lovrin 10 had similar root biomass to and lower shoot biomass than Jing 411. Increasing P supply from 32 to 161 lM resulted in lower tissue As concentrations, and increasing As s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 24 publications
8
23
0
Order By: Relevance
“…The higher P levels in soil that resulted from bran-char addition may partially account for the increase in the transfer coefficient of As with bran-char treatment. It has been reported that increasing the P supply increased the root-to-shoot translocation of As in two cultivars of winter wheat (Geng et al 2006). However, this explanation is not sufficient because the pathway of As translocation in higher plant functions involves As sequestration in the vacuoles and As loading and unloading in the xylem and phloem; enzymes responsible for arsenate reduction and methylation are as yet poorly understood (Zhao et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…The higher P levels in soil that resulted from bran-char addition may partially account for the increase in the transfer coefficient of As with bran-char treatment. It has been reported that increasing the P supply increased the root-to-shoot translocation of As in two cultivars of winter wheat (Geng et al 2006). However, this explanation is not sufficient because the pathway of As translocation in higher plant functions involves As sequestration in the vacuoles and As loading and unloading in the xylem and phloem; enzymes responsible for arsenate reduction and methylation are as yet poorly understood (Zhao et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment means showed the maximum value (23.07 mm) in case of T2 (4 mg/L arsenic) using sodium arsenite (Table 2 and Figure 4) which is 130.9% of control (17.62 mm). This reveals that low concentrations of arsenic increase the seedling growth up-to certain limit but after that more increase in concentration inhibits the seedling growth (Liu and Zhang, 2007;Geng et al, 2006) as least value (14.56 mm) was recorded in highest concentration (10 mg/L) of sodium arsenite. Sunflower cultivars behaved differently (Table 3) in case of plumule length as out of different sunflower cultivars H3 (FH-405) gave maximum plumule length (25.17 mm) whereas least value (13.2 mm) was observed in H1 (FH-331).…”
Section: Plumule Length (Mm)mentioning
confidence: 99%
“…Due to the limiting conditions of this soil for the support of plant development, the As uptake and transport to shoots may be favored, as has been observed in phosphorous-deficient conditions in several plant species (Esteban et al, 2003;Geng et al, 2006;Abbas et al, 2008).…”
Section: Figure 3 Herementioning
confidence: 99%